Adsorption Behaviour of Hazardous Dye (Methyl Orange) on Cellulose-Acetate Polyurethane Sheets. Issue 1 (May 2020) - Iqhrammullah, M; Marlina,; Nur, S
Abstract: Cellulose Acetate-Polyurethane (CA-PU) copolymer has been successfully prepared by a simple blending method and examined for its adsorption capacity against Methyl Orange (MO). Functional group characterization using Fourier Transform-Infrared (FTIR) confirms the urethane linkage formation as well as the presence of several essential functional groups (such as; O-H, C=O, and aromatic ring). Surface morphology changes are also observed using Scanning Electron Microscopy (SEM), where a smoother and porous structure is obtained in CA-PU. The adsorption isotherm is examined with Langmuir, Freundlich, Halsey, and Harkin-Jura models. MO adsorption on CA-PU sheets fits Freundlich isotherm (R 2 = 0.9722) with KF = 279.45 mg/g. Kinetics studies of the adsorption with pseudo first-order and pseudo second-order plots exhibit that chemisorption is the adsorption limiting-rate.